FOTODEGRADASI FENOL DALAM LEMPUNG TERPILAR TIO2 (PHOTODEGRADATION OF PHENOL ON TIO2-PILLARED-KAOLINITE - Imelda H Silalahi; Nelly Wahyuni; Irwan Irwan (Indonesian Journal of Pure and Applied Chemistry, 2020)
Photodegradation of phenol on TiO2-pillared-kaolinite was observed. Pillarization of kaolinite was conducted through intercalation of polyoxotitanium sol into clay suspension followed by calcination giving TiO2-kaolinite which showed an increase in specific surface area and total pore volume compared with the kaolinite. The analysis of XRD demonstrated no significant change on d-space of second order of kaolinite structure associated with 2q 26.61°, but diffractions with regard to 2q 25.3° and 48.0° interpreted for TiO2 anatase were seen on the diffractogram of TiO2-kaolinite. The significant decrease of phenol concentration was observed in the presence of both kaolinite and TiO2-kaolinite under UV illumination (hn  ³ 365 nm) compare with the photoreaction without the kaolinite materials however the degradation rate of phenol on TiO2-kaolinite was faster than that on the kaolinite-only where 50% of phenol was consumed after 45 minutes of reaction. Kinetic study showed the photoreaction of phenol on TiO2-kaolinite follows the first order reaction with the reaction rate constant of 1.8 x 10-2 min-1.